2012
DOI: 10.4062/biomolther.2012.20.1.068
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Extracts from Black Soybean (Glycine max L.) Protect Human Glial Cells Against Oxygen-Glucose Deprivation by Promoting Autophagy

Abstract: Anthocyanins have received growing attention as dietary antioxidants for the prevention of oxidative damage. Astrocytes, which are specialized glial cells, exert numerous essential, complex functions in both healthy and diseased central nervous system (CNS) through a process known as reactive astrogilosis. Therefore, the maintenance of glial cell viability may be important because of its role as a key modulator of neuropathological events. The aim of this study was to investigate the effect of anthocyanin on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Blueberries are a rich source of anthocyanins and have been shown to act on autophagy regulating proteins such as mTOR (Kim et al, 2012). Similarly, strawberries, which contain high amounts of phenolic acids and ellagitannins, also have been shown to improve neuronal signaling via their antioxidant and anti-inflammatory mechanisms (Miller and Shukitt-Hale, 2012).…”
Section: Phf-tau-frontal Cortexmentioning
confidence: 98%
“…Blueberries are a rich source of anthocyanins and have been shown to act on autophagy regulating proteins such as mTOR (Kim et al, 2012). Similarly, strawberries, which contain high amounts of phenolic acids and ellagitannins, also have been shown to improve neuronal signaling via their antioxidant and anti-inflammatory mechanisms (Miller and Shukitt-Hale, 2012).…”
Section: Phf-tau-frontal Cortexmentioning
confidence: 98%
“…To address this issue, we used ATCs extracted from black soybeans (cv Cheongja 3). These ATC extracts were shown to promote apoptosis in a model of prostate hyperplasia in vivo and to induce autophagy in glial cells, which proved to contain biologically active components of autophagy induction as well as apoptosis (14,24). In the present study, we observed the induction of autophagy and AMPK activation by ATCs and analyzed the role of AMPK in this autophagy.…”
Section: Kip1mentioning
confidence: 74%
“…Based on these apoptosis-inducing and anti-inflammatory as well as anti-invasive and anti-angiogenic effects (9,10), attempts have been made to develop ATCs as a chemopreventive agent, and promising results of pilot studies in rodent models of esophageal and colorectal cancers and human colorectal cancer patients have provided support for this hypothesis (11,12). In addition to inducing apoptosis, it has been suggested that ATCs induce autophagy in cancer and glial cells (13,14), although the mechanism for this remains to be clarified. Autophagy is considered to be a cellular defense system that can protect cancer cells from anticancer therapeutics.…”
Section: Anthocyanins In the Black Soybean (Glycine Max L) Protect Umentioning
confidence: 99%
“…After stroke, astrocytes tend to rupture, leading to an imbalance in glutamate absorption and release and an increase in pro-apoptotic factors, which may ultimately accelerate the death of peripheral neurons [30,31]. Oxidative stress is the basis of the pathogenesis of stroke.…”
Section: Discussionmentioning
confidence: 99%